KAJIAN WAKAF DALAM KITAB AL-MUHALLA DAN RELEVANSINYA DENGAN KETENTUAN WAKAF DI INDONESIA - Rahmat Hidayat (Muqaranah, 2020)
Theoretical studies of waqf have often featured the opinions of scholars from Sunni schools, such as the Hanafi, Shafi'i, Maliki, and Hanbali schools. While the opinions of other schools of waqf, such as the Zahiri school, which was promoted by Ibn Hazm in al-Muhalla, are rarely studied. The purpose of this study is to find out the provisions of waqf in Kitab al-Muhalla and their relevance to the provisions of waqf in Indonesia. To achieve this goal, the author uses normative legal research that focuses on one book of the Zahiri School. The primary source is Kitab al-Muhalla, while the secondary source is the book or article relevant to this study. The results showed that the discussion of waqf in Kitab al-Muhalla only presents general views on waqf theory such as definitions, waqf objects, waqf ownership, expert waqf and ta'bid requirements on waqf. While specific studies on nazhir (waqf management), waqf management, waqf dispute resolution are not highlighted. Some waqf theories in Kitab al-Muhalla are relevant to waqf provisions in Indonesia, including ownership of waqf property, and expert waqf. While other provisions are not relevant to be applied in Indonesia. This phenomenon is natural, considering that the Zahiri school only sees zahir nash in studying waqf. Meanwhile, waqf studies today focus more on the ijtihadi approach.